Symptomatic Coronary Anomalies and Ischemia in Teenagers – Rare but Real - Borns, Julia; Gräni, Christoph; Kadner, Alexander; Gloeckler, Martin; Pfammatter, Jean-Pierre (Frontiers in Cardiovascular Medicine, 2020)
Three cases of teenagers with anomalous aortic origin of the coronary arteries (AAOCA) are presented with typical exercise induced symptoms (chest pain, syncope or dizziness). Using multimodal imaging, diagnoses was confirmed showing interarterial and/or intramural course of the coronary artery explaining the ischemia induced symptoms. Successful surgical correction with unroofing of the AAOCA was performed in all three cases with a favorable outcome. Even though AAOCA are rare, some variants may be relevant and potentially life threatening, therefore treating physicians should be aware of correctly diagnosing and treating these individuals.